Nutriomics-specific chromatogram of aromatic herbs to mitigate methane emission through in vitro ruminal fermentation - Ahmed, S.; Wu, J.; Liu, Z.; Jiang, A.; Pu, X.; Zhou, C.; Lukuyu, Ben A.; Kang, J.; Tan, Z. (Elsevier, 2025)
Methane is considered as a potent greenhouse gas, emitted from ruminants through enteric fermentation. Several methane mitigation strategies have been proposed and reported, however, role of aromatic herbs and their bioactive components on elimination of methane is still unclear.